Telemedicine in Oncology: Delivering on an Overdue Promise in the COVID-19 Era - West, Howard (Jack) (Frontiers in Oncology, 2020)
The coronavirus pandemic and enforced physical distancing unleashed a perfect storm have made it an ideal setting for telemedicine. With the recognition that merely venturing out from home, particularly to a hospital or clinic with patients and health care professionals (HCPs), is accompanied by real risk of exposure to coronavirus that appears to be disproportionately affect patients with cancer and other comorbidities,5,6 the latent potential of telemedicine emerged as a solution. To their credit, the Center for Medicare and Medicaid Services (CMS) rapidly developed sweeping changes to federal regulations for telemedicine that guaranteed coverage of 80 services that could be delivered by telemedicine and even telephone-based visits and be reimbursed at parity with that provided for a live visit in the clinic.7,8 The revised standards also specifically relaxed regulation of HIPAA compliance and states that physicians can communicate with patients through popular and readily accessible platforms like Facebook and Skype. States are currently in the ongoing process of revising and relaxing their restrictions on the practice of telemedicine, while also working to ensure parity of payment for telemedicine with live services in order to both enable patients to receive care from home in order to reduce risk of exposure to coronavirus and to allow HCPs to work from home or other settings apart from those with higher risk of themselves being infected.9